Should MRI replace mammography as the initial screening modality for asymptomatic women aged 18 – 45 years at high risk of developing breast cancer? A systematic review - Akpaniwo, GM; Boynes, S; Danfulani, M; Chigozie, NI; Umar, A (Asian Journal of Medical Sciences, 2016)
Background: Breast cancer occurs in both men and women, although it is more prevalent among women. Mammography is generally the diagnostic imaging modality of choice, but it is limited in the detection of breast cancer in young women, aged 18-45 years due to the dense nature of their breast tissue. Aims and Objectives: This review explores whether MRI should replace mammography as the initial screening modality for asymptomatic women, aged 18-45 years at high risk of developing breast cancer. Materials and Methods: A systematic review of the literature was undertaken. A search of Medline, Pubmed central, Cinahl and Google scholar for English language literature from 2004 to 2015 was undertaken. Also a review of reference lists, author searching and review of NICE evidence base for exiting guidelines was done. Included studies were assessed for bias using STARD quality assessment tool and data were extracted systematically using a purposefully designed data extraction form. Result: From the seven included studies, 179 participants of the total population had breast cancer and a total of 199 breast cancer was detected by both modality used. MRI detected a total 148 breast cancers compared to 78 detected by mammography, and 10 interval cancer was reported. Sensitivity estimate from the included studies ranged from 25% to 100% while specificity ranged from 79% to 99%. MRI detected more breast cancer but had a moderate specificity compared to mammography as reported in the literature. Conclusion: In the absence of contraindication and accessibility, MRI should be used as the initial screening modality for asymptomatic women aged 18 – 45 years, at high risk of developing breast cancer. Asian Journal of Medical Sciences Vol.7(5) 2016 1-9